Assessing the Impact of ICT and the Transition from 2G to 5G on CO₂ Emissions - Porapan Juthong; Suttiwit Saringkarnpoonperm; Chate Khemakongkanont (International Telecommunications Society (ITS), 2025)
This study examines the environmental impact of global ICT expansion, focusing on CO² emissions across 173 countries from 2000 to 2021 using a one-step difference GMM. The findings reveal a two-phase relationship: Early-stage ICT deployment tends to increase emissions; however, as adoption expands, emissions are significantly reduced. The environmental impact of upgrading to 4G/5G networks is not uniform. For nations primarily reliant on 2G/3G infrastructure, the transition yields immediate environmental benefits. Conversely, in advanced ICT nations, the rollout may initially increase emissions, an effect that is later offset by substantial long-term reductions. The study concludes that ICT development does not automatically guarantee environmental benefits. Strategic policies—such as managing the full life cycle of ICT infrastructure from production to disposal, promoting renewable power in the ICT sector, and phasing out legacy networks— are essential to align ICT growth with decarbonization goals.
Keywords: 330; ICT; Mobile Cellular Network; CO² Emissions